Implementasi Media Pembelajaran Papan Pintar dalam Pembelajaran IPS Kelas IV SDN Kuin Utara 6 Banjarmasin - Syaidati Elida; Rahmi Nur Aini; Santia Rahmah; Aldy Ferdiyansyah (Journal of Character and ELementary Education, 2026)
This study aims to describe the implementation of the PapinPST (Primary–Secondary–Tertiary Smart Board) learning media in fourth-grade social studies learning at SDN Kuin Utara 6 Banjarmasin and to analyze the improvement of students’ engagement, motivation, and understanding. The scope of the research focuses on the use of interactive learning media in teaching primary, secondary, and tertiary human needs in elementary social studies education. This study employed a qualitative approach using a case study method. Data were collected through classroom observations, interviews with teachers and students, and documentation during the learning process. Data analysis was conducted thematically through transcription, coding, and interpretation, while data validity was strengthened through source triangulation. The findings indicate that the implementation of PapinPST learning media increased students’ active participation, created a more enjoyable learning atmosphere, and helped students understand the concept of human needs in a more concrete and visual manner. In addition, the media also encouraged collaboration, communication, and students’ confidence in expressing their opinions. The implementation of PapinPST helped overcome the limitations of conventional social studies learning, which had previously relied heavily on lecture methods and traditional media. Therefore, PapinPST can serve as an innovative and practical solution to support interactive, contextual, and student-centered social studies learning in accordance with the Merdeka Curriculum in elementary schools.